2020
DOI: 10.1371/journal.pone.0242020
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the success of active and passive restoration in a tropical cloud forest landscape: A multi-taxa fauna approach

Abstract: Tropical forest restoration initiatives are becoming more frequent worldwide in an effort to mitigate biodiversity loss and ecosystems degradation. However, there is little consensus on whether an active or a passive restoration strategy is more successful for recovering biodiversity because few studies make adequate comparisons. Furthermore, studies on animal responses to restoration are scarce compared to those on plants, and those that assess faunal recovery often focus on a single taxon, limiting the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
(95 reference statements)
3
30
1
Order By: Relevance
“…There is little consensus on whether active or passive restoration strategies are more successful for recovering biodiversity because few studies make adequate comparisons [41]. In some studies, recovery of species' richness and composition is similar in active-and passive-restoration sites, while in others, recovery of forest specialists is enhanced through active restoration [40,41].…”
Section: Passive-restoration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little consensus on whether active or passive restoration strategies are more successful for recovering biodiversity because few studies make adequate comparisons [41]. In some studies, recovery of species' richness and composition is similar in active-and passive-restoration sites, while in others, recovery of forest specialists is enhanced through active restoration [40,41].…”
Section: Passive-restoration Methodsmentioning
confidence: 99%
“…There is little consensus on whether active or passive restoration strategies are more successful for recovering biodiversity because few studies make adequate comparisons [41]. In some studies, recovery of species' richness and composition is similar in active-and passive-restoration sites, while in others, recovery of forest specialists is enhanced through active restoration [40,41]. While both restoration strategies may lead to different vegetation structures, they may support similar biomass of foliage-dwelling arthropods and be similarly used by foraging insectivorous birds [40].…”
Section: Passive-restoration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This question is particularly germane as we enter 2021-2030 which the United Nations General Assembly has declared as the "Decade on Ecosystem Restoration" [31]. There is much controversy over the relative successes of "active" vs. "passive" restoration, but few studies have focused on animals and their responses to forest recovery [32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Broughton et al [4] found that secondary woodlands in England that were adjacent to ancient woodlands recovered naturally over a period of a few decades. Díaz-García et al [10] compared recovery of amphibians, ants, and dung beetles in naturally regenerating and actively planted tropical forests in Mexico; they found that passive and active restoration approaches were similarly effective in restoring species richness of all guilds, but that forest specialists were enhanced through active planting. In contrast, other studies show that intensive anthropogenic interventions such as transplanting corals (Ferse et al [11]), or controlling invasive species and reintroducing fauna (Roberts et al [12]) are necessary to facilitate recovery.…”
mentioning
confidence: 99%